Formulasi Krim Ekstrak Etanol Herba Krokot (Portulacca oleracea L.) sebagai Tabir Surya - Ani Hartati (Jurnal Kesehatan, 2019)
The use of sunscreen is a way to prevent the adverse effects of sun exposure to the skin. Sunscreens that contain synthetic chemical compounds can cause allergies to the skin. Therefore it is necessary to look for other ingredients that have activities as sunscreens, one of which is by using natural ingredients, especially from plants such as purslane herbs that have these activities. This type of research is an experiment to formulate cream of ethanol extract of purslane herbs as sunscreens with concentrations of 0%, 0.5%, 0.75%, and 1.0%. The thick extract of purslane herb is formulated as a cream with a base of stearic acid cream, cetyl alcohol, glycerin, triethanolamine, with nipagin and nipasol preservatives. Furthermore, the cream was carried out several tests, namely organoleptic test, homogeneity, pH, spreadability, stability, cream type, and SPF value in vitro. The test results found that the formulated cream had a light brown-green color, with a distinctive odor and half solid consistency. A cream that is made homogeneous, all creams are alkaline. All the spread cream meets the requirements (more than 4 cm). All cream formulas are stable because there is no separation in the cycling test. This type of cream is a type of oil in water that is easy to wash. SPF value of F0 cream (0% purslane ethanol extract) was 0.620±0.070, F2 (0.5% extract) 4.341±0.565, F3 (0.75% extract) 5.289±0.644, and F3 (1.0% extract) 7,862±1,564.